Cyprus as one of the most attractive offshore areas for Ukraine - Maziar, Olga; Bozhok, Natalia (My University, 2019)
In the scientific paper the definition of the term “offshore” was analyzed. The largest offshore zones in the world were identified. The dynamics of direct foreign investments from Ukraine to other countries of the world for 2015-2017 were interpreted. The reasons of Cyprus's attractiveness for Ukraine as an offshore zone and influence of capital outflow from Ukraine to its economy were determined.
Keywords: foreign direct investment; offshore zone; taxation; capital; офшорна зона; прямі іноземні інвестиції; оподаткування; капітал; кафедра ділової іноземної мови та міжнародної комунікації